EPISTEMOLOGICAL TRENDS IN ENGLISH EDUCATION RESEARCH: A CONTENT ANALYSIS OF UNDERGRADUATE AND POSTGRADUATE THESES (Proceedings of English Linguistics and Literature, 2022)
Research in English Language Education has developed over the past decades along with the rapid growth of English Language Teaching and Learning due to technological innovation and globalization. One of the essential elements of a research is its methodology. Research methodology represents the epistemological aspects, the nature of the research, and the objects being explored in it. Hence, a study focusing on the use of research methods is worth discussing further. In an attempt to discover the trends in English Language Education research, particularly in its epistemological aspect, this study reviews 150 research consisting of undergraduate and postgraduate theses in the three-year period of 2019 to 2021. Using content analysis, this study found the trends through the highest frequency identified in the data collection and the findings were also interpreted and added with meanings. By investigating a series of current research on English Language Education theses, the results are expected to contribute to the knowledge of English Language Education research for students, teachers, and academicians.